Facts about Phosphorus - Nancy J. Gal; Wendy J. Dahl (EDIS)
Phosphorus is a mineral found in every cell of the body, usually in the form of phosphate. It is the second most abundant mineral in the body after calcium. About 85% of phosphorus is stored in the bones and teeth. It is important for forming bones and teeth, as well as repairing bones. This 3-page fact sheet was written by Nancy J. Gal and Wendy J. Dahl, and published by the UF Department of Food Science and Human Nutrition, November 2013.